2008
DOI: 10.1038/ni.1641
|View full text |Cite
|
Sign up to set email alerts
|

The BTB–zinc finger transcriptional regulator PLZF controls the development of invariant natural killer T cell effector functions

Abstract: Invariant Natural Killer T cell (iNK Tcell) have an innate immunity-like rapidity of response and the capacity to modulate effector functions of other cells. We show that the BTB-ZF transcriptional regulator, PLZF, is specifically expressed in iNKT cells. iNKT cells develop in the absence of PLZF, but lack many innate T cell features. PLZF deficient iNKT cells accumulate in the lymph nodes rather than in the liver and do not have an activated phenotype or express NK markers. PLZF deficient iNKT cells do not se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

24
615
1
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 502 publications
(651 citation statements)
references
References 64 publications
(72 reference statements)
24
615
1
2
Order By: Relevance
“…2,3,7,9,11 Recently, an intriguing role of PLZF in immune system has been described. 16,17 Innate T cells bridges the innate and adaptive immune systems, including gdT cells and several subsets of abT cells. In general, innate T cells (of an ab T-cell lineage) develop in the thymus from double-positive progenitors.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…2,3,7,9,11 Recently, an intriguing role of PLZF in immune system has been described. 16,17 Innate T cells bridges the innate and adaptive immune systems, including gdT cells and several subsets of abT cells. In general, innate T cells (of an ab T-cell lineage) develop in the thymus from double-positive progenitors.…”
Section: Discussionmentioning
confidence: 99%
“…27 PLZF is essential for the development of invariant NKT cells with acquisition of their unique innate-like properties in a mouse system. 16,17 Recently, our group and others have reported a new distinct subset of innate abT cells (T-T CD4 T cells), which are selected by MHC class II-expressing thymocytes and also depend on PLZF for their development. [28][29][30] Moreover, we reported that the generation of T-T CD4 T cells is a physiological process in humans.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The deficiency of E protein transcription factor HEB seriously blocked the development of NKT cells at the stage 0 but made no difference to conventional T cells because it failed to regulate thymocyte survival or distal rearrangements of the TCRα chain [34] . Promyelocytic leukemia zinc finger transcription factor (PLZF) is responsible for the early stages (stage 1 to 2) of NKT cell maturation and production of the functional cytokines, even in the absence of SLAM-SAP-Fyn signaling [35,36] . Recently, the identification of selective function for the transcription factor early growth response 2 (Egr2) in maturation and homeostasis of NKT cells also emphasizes the importance of the calcineurin-NFAT-Egr2 pathway in the development of NKT cells.…”
Section: Controls Of Nkt Cell Development and Homeostasismentioning
confidence: 99%